Art and ideas about Nature - Jaime Carbonel, Alejandro (2018)
This essay reflects on the different conceptual perspectives of what we understand by Nature and how they shape our reality and our collective tasks. This reflection starts from the artistic field and then incorporates aspects of political ecology in the Human / Nature dialectic, emphasizing the common points and the intersections that we consider interesting. We take three examples in the history of recent art where we identify the conceptual problems around the configuration of the idea of ??the natural. First, we will develop aspects of the intersection between art and science in encyclopedic projects and the impact of cartography as the image that embodies this intersection. The second example presents a renewed look towards the natural with the entropic landscape of Robert Smithson. The third example, the artwork of Stelarc, reconfigures the Natural before the technological impact of human development. These references serve to illustrate and develop the debate of contemporary ideas about the cultural construction of Nature through art and how this debate takes shape and is disseminated through political channels that share or resist the programs of power for the permanent configuration of the representations of the world.